The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1016/s1054-3589(08)57007-4
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Drugs to Treat Cocaine Dependence: Behavioral and Neurochemical Effects of Atypical Dopamine Transport Inhibitors

Abstract: Stimulant drugs acting at the dopamine transporter (DAT), like cocaine, are widely abused, yet effective medical treatments for this abuse have not been found. Analogs of benztropine (BZT) that, like cocaine, act at the DAT have effects that differ from cocaine and in some situations block the behavioral, neurochemical, and reinforcing actions of cocaine. Neurochemical studies of dopamine levels in brain and behavioral studies have demonstrated that BZT analogs have a relatively slow onset and reduced maximal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
69
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 100 publications
3
69
0
Order By: Relevance
“…Several mechanisms have been suggested for the antagonism by BZT analogs of the effects of cocaine (Hiranita et al, 2009;Tanda et al, 2009a). Previous studies examined the potential role of muscarinic or histaminic antagonist effects, though studies conducted to date provide little evidence that those actions can account for the antagonism of cocaine (Tanda et al, 2009b), and presumably that of d-methamphetamine. Nonetheless, specific binding of radiolabeled JHW007 has shown that it binds to sites other than the DAT, and that binding is not fully displaceable by M 1 or H 1 ligands, indicating still other sites as potentially contributing to the antagonist effects of BZT analogs (Kopajtic et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms have been suggested for the antagonism by BZT analogs of the effects of cocaine (Hiranita et al, 2009;Tanda et al, 2009a). Previous studies examined the potential role of muscarinic or histaminic antagonist effects, though studies conducted to date provide little evidence that those actions can account for the antagonism of cocaine (Tanda et al, 2009b), and presumably that of d-methamphetamine. Nonetheless, specific binding of radiolabeled JHW007 has shown that it binds to sites other than the DAT, and that binding is not fully displaceable by M 1 or H 1 ligands, indicating still other sites as potentially contributing to the antagonist effects of BZT analogs (Kopajtic et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Worldwide estimates put the number of regular cocaine users at nearly 20 million (United Nations Office on Drugs and Crime, 2014). Despite longstanding efforts to develop pharmacotherapies (Mello, 1990;Roberts and Brebner, 2000;Platt et al, 2002;Dackis and O'Brien, 2003;Grabowski et al, 2004;Vocci et al, 2005;Tanda et al, 2009), there are currently no approved medications for treating cocaine abuse.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, methamphetamine reverses DA translocation by DAT to increase extracellular DA concentrations leading to reward (Fischer and Cho, 1979;Liang and Rutledge, 1982;Wise and Bozarth, 1987;Di Chiara and Imperato, 1988). Numerous studies have focused on DAT as a therapeutic target for the development of treatments for psychostimulant abuse (Grabowski et al, 1997;Dar et al, 2005;Howell et al, 2007;Tanda et al, 2009). However, this approach to drug discovery has thus far not resulted in viable efficacious therapeutics for methamphetamine abuse.…”
Section: Introductionmentioning
confidence: 99%